Neutrophils and Macrophages: the Main Partners of Phagocyte Cell Systems - Silva, Manuel T.; Correia-Neves, Margarida (Frontiers in Immunology, 2012)
Biological cellular systems are groups of cells sharing a set of characteristics, mainly key function and origin. Phagocytes are crucial in the host defense against microbial infection. The previously proposed phagocyte cell systems including the most recent and presently prevailing one, the Mononuclear Phagocyte System (MPS), grouped mononuclear cells but excluded neutrophils, creating an unacceptable situation. As neutrophils are archetypical phagocytes that must be members of comprehensive phagocyte systems, M. T. Silva recently proposed the creation of a Myeloid Phagocyte System (MYPS) that adds neutrophils to the MPS. The phagocytes grouped in the MYPS include the leukocytes neutrophils, inflammatory monocytes, macrophages and immature myeloid DCs. Here the justifications behind the inclusion of neutrophils in a phagocyte system is expanded and the MYPS are further characterized as a group of dedicated phagocytic cells that function in an interacting and cooperative way in the host defense against microbial infection. Neutrophils and macrophages are considered the main arms of this system.